Strategic energy management plan and MS ISO 50001:2011 compliance / Mohd Tarmizi Mat Asim...[et al.] - Mat Asim, Mohd Tarmizi; Tengku Ibrahim, Tengku Muhammad Fahmi; Adam, Nor Mariah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Strategic energy management plan is a long-term approach provided for achieving the goals set, determining the level of energy efficiency, detecting, controlling, monitoring and reporting on the performance of energy consumption. Successful strategic energy management plan builds long-term relationships with energy users and can improve the persistence of energy savings. It will also benefit the organization, the country and the world directly and indirectly. However, without the support, these benefits may not be achieved and the implementation of strategic energy management plan will not be successful. The objective of the study is to improve energy performance at TH Headquarters building and to reduce electricity energy consumption. The study started with preliminaries study, data collection, data analysis and strategic energy management plan development process. All data and information were sourced from data collection activity that has been processed and analyzed based on the needs such as occupant behavior, trend of energy used and energy performance. Furthermore, wastage factors, target saving baseline, energy performance indicator, and strategic energy management plan were identified and developed. The proposed methods refer to MS ISO 50001:2011 as a guideline.